bagaimana Efek dari Limbal Relaxing Incision terhadap hasil K1 dan K2 1 minggu setelah operasi - Bakhri, ilham Prayoga; Sadasih, Wisnu; Fanany, A. Rizal (Majalah Oftalmologi Indonesia, 2023)
Introduction: Limbal Relaxing Incisions (LRI) is a surgical technique used to correct astigmatism during cataract surgery. This technique used to reduce the steepness of the corneal curvature in a particular meridian. LRI can be performed alone or in combination with phacoemulsification.  Methods: This prospective study aimed to investigate the effect of Limbal Relaxing Incisions (LRI) on corneal astigmatism in patients who underwent phacoemulsification cataract surgery. Five patients were included in this study, and preoperative and 1-week postoperative keratometry values (K1=flat keratometry and K2=steep keratometry) were measured using the IOL Master. Paired t-test analysis was used to compare the changes in K1 and K2 values before and after LRI.  Results: Five patients with the mean age 39.8 years (range: 22 to 76 years) and corneal astigmatism 3.12 D (range: 2.25 to 4.66 D) were underwent LRI and cataract surgery. The mean preoperative K1 and K2 values were 42.12 D and 46.44 D, respectively, while the mean 1-week postoperative K1 and K2 values were 42.60 D and 45.80 D, respectively. Paired t-test analysis showed a statistically significant decrease in K2 values (p = 0.025) but no significant change in K1 values (p = 0.329).  Conclusion: This study showed there were no significant difference between pre and postoperative of K1 and showed a significant decrease in K2 on IOL Master examination. The wide age range of the included patients may have influenced the effectiveness of LRI in reducing astigmatism. Further study with more subjects are required.